Pengaruh Retribusi Pariwisata dan Penerimaan Pajak Restoran Terhadap Pendapatan Asli Daerah Kabupaten Maros - Ahmad Ahmad; Nisma Ariskha Masdar (Program Studi Administrasi Fiskal, 2025)
ABSTRACT This study is motivated by the importance of the tourism and restaurant sectors in increasing the Regional Original Income (PAD) of Maros Regency. The purpose of this study is to determine the effect of tourism levies and restaurant tax revenues on PAD of Maros Regency partially and simultaneously. This study uses a quantitative method with secondary data from BAPENDA and DISPAPORA of Maros Regency in 2022–2024. The results of multiple linear regression analysis show that simultaneously, tourism levies and restaurant tax revenues have a significant effect on PAD, with an F count of 14.773 and a significance of 0.000 <0.05. Partially, only the restaurant tax variable has a significant effect on PAD with a t count of 5.432> ttable 2.035 and a significance of 0.000. Meanwhile, tourism levies do not have a significant effect on PAD (t count 0.375 <t table) or on restaurant tax revenues (t count -0.610). The regression equation obtained is Y = 0.453 + 0.027X1 + 1.056X2. The conclusion of this study is that restaurant tax revenue has a dominant role in increasing the PAD of Maros Regency, while tourism levies have not shown a significant effect individually.